The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1136/mp.52.3.140
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in colorectal cancer

Abstract: Background-The process of metastasis is complex, involving many interrelated stages, including proteolysis. Proteolysis occurs in both normal and pathological processes and involves the breakdown of the extracellular matrix and/or basement membrane by proteolytic enzymes. Normally, proteolysis is tightly controlled by specific endogenous proteinase inhibitors. However, in certain disease processes, including cancer, controlled but abnormal proteolysis seems to occur. Proteinases involved in tumour invasion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
1
18
1
1
Order By: Relevance
“…By the use of a specific MMP inhibitor as a control in this activity assay and the use of a general protease inhibitor, only actual active MMPs are measured and not other proteinases or protein-inhibitor complexes. This is an important difference with assays used by others (Garbett et al, 1999b;Baker et al, 2000;McKerrow et al, 2000). The results obtained here indicate that in the tumours studied MMP (production and) activation is elevated compared to the production of TIMPs.…”
Section: Molecular and Cellular Pathologycontrasting
confidence: 55%
“…By the use of a specific MMP inhibitor as a control in this activity assay and the use of a general protease inhibitor, only actual active MMPs are measured and not other proteinases or protein-inhibitor complexes. This is an important difference with assays used by others (Garbett et al, 1999b;Baker et al, 2000;McKerrow et al, 2000). The results obtained here indicate that in the tumours studied MMP (production and) activation is elevated compared to the production of TIMPs.…”
Section: Molecular and Cellular Pathologycontrasting
confidence: 55%
“…The overexpression of the TIMP-1 protein in cancer cells has also been confirmed in molecular studies [14,15]. However, the analyses of tissue homogenates obtained from the patients diagnosed with CRC with the ELISA method indicated that the level of TIMP-1 protein increased in comparison to its concentration in normal colon tissue in biological material of this type [16][17][18]. Furthermore, Baker et al [17] noted that the growth of TIMP-1 in tumor homogenates was closely connected with Duke's cancer stage, lymph node involvement and MMP-1 level.…”
Section: Discussionmentioning
confidence: 83%
“…Treatment with gelatinase inhibitors significantly nullified the invasiveness of WiDr cells (Fig. 4B), indicating the involvement of hydrolysis of the basement membrane catalyzed by MMP-2 and/or MMP-9 (21,22). In view of the result that the cell invasion rate was nearly the same among mock cells of TIMP-1 transfectant (Fig.…”
Section: Establishment Of Stable Transfectants Of Timp-1 and The Glycmentioning
confidence: 82%